News Web Easy as Japanese Learning Media - Arianingsih, A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to describe the function of News Web Easy as Japanese learning media and students’ perceptions of this media. This research used a descriptive method with a sample of 20 persons of UNIKOM Japanese Department students in the 2020/2021 academic year. The research instrument is a questionnaire and literature studies. The results show that the perceived ease of use and perceived usefulness of this media are high, so the intention to use this media becomes high following the Technology Acceptance Model. News Web Easy can be used as an alternative for Japanese language learning which can not only improve Japanese language skills but also can help to know about the latest news about Japan in simple Japanese.